A new form of genetic female sterility in capsicum annuum L. - Wilson, G.F.; Fatokun, C.A.; Adeniran, M.O. (1982)
During evaluation of genotypes of pepper (Capsicum annuum L.), a female-sterile mutant was observed in one line. The mutant also exhibited flat stem and rosette branching-habit. The stamens were functional and pollen fertility was normal. Style and stigma were petaloid and non-functional. A single recessive gene caused the sterility and the other aberrant characteristics. The possible use of this mutant in a hybrid seed production programme in pepper is indicated.